Combining State-based and Scenario-based Approaches in Modeling Biological Systems - Fisher, Jasmin; Harel, David; Hubberd, Jane Albert; Peterman, Nir; Stern, Michael J.; Swerdlin, Naamah (Proc. of Computational Methods in Systems Biology (CMSB '04), Lecture Notes in Bioinformatics, 2004)
Biological systems have recently been shown to share many of the properties of reactive systems. This observation has led to the idea of using methods devised for the construction (engineering) of complex reactive systems to the modelling (reverse-engineering) of biological systems, in order to enhance biological comprehension. Here we suggest to combine the two formal approaches used in our group— the state-based formalism of statecharts and the scenario-based formalism of live sequence charts (LSCs). We propose that biological observations are better formalized in the form of LSCs, while biological mechanistic models would be more natural to specify using statecharts. Combining the two approaches would enable one to verify the proposed mechanistic models against the real data. The biological observations can be compared to the requirements in an engineered system, and the mechanistic model would be analogous to the implementation. While requirements are used to design an implementation, here the observations are used to motivate the invention of the mechanistic model. In both cases consistency of one with the other must be established, by testing or by formal verification.